Implikasi Kepailitan Suatu Perusahaan terhadap Perlindungan Hukum Bagi Investor di Pasar Modal - Saputra, Angga (Media Hukum Indonesia (MHI), 2025)
Abstract: The capital market is an alternative to economic financing that all levels of society have started to touch.  It is important for the government as the highest authority to provide legal certainty and protection in order to protect the interests of its people.  Investing in the capital market in the form of shares is an investment option.  Stock investment is an alternative financing for companies in the country, especially publicly listed companies that have been listed on the capital market, but investing in the capital market in the form of shares, apart from providing profit opportunities, also has risks, among others, the company will go bankrupt.  This paper aims to determine the legal consequences of a public company going bankrupt on capital market investors and legal protection for capital market investors in public company bankruptcy in terms of capital market law.  The bankruptcy of a public company has an impact on the ownership of shares of investors in a public company, that is, it raises the risk of loss in the form of capital loss, which is caused by being locked or cannot be transacted due to the delisting process by the stock exchange.  Legal protection that can be taken by investors in this condition is to take preventive measures through the intermediary of Otoritas Jasa Keuangan  (OJK) as the authority in the capital market